MENUJU SISTEM PEREKONOMIAN INDONESIA - Dawam Rahardjo, M. (Unisia, 2012)
This article proposes to elaborate on the development of Indonesian economic system since the independence to the more recently, known as Pancasila Economic System. Mubyarto identifies some characteristics of the system as follow. Firstly, economic wheel is driven by economic, moral and social incentives. Secondly, based on humanity principle, egalitarianism is a strong will of all people to reach equality. Thirdly, the priority of economic policy is to create strong national economy, meaning that nationalism has been a spirit of every economic policy. Fourthly, cooperative society is the backbone of economy and the most concrete form of economic cooperation. Finally, there must be a balance of planning between that in national and decentralization levels in implementing economic activities to reach economic and social justice. Keywords: economic system, characteristics, national, decentralization, justice.